2018
DOI: 10.1007/s00115-018-0521-5
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der Personalbesetzung auf Konflikte auf psychiatrischen Stationen

Abstract: Acute psychiatric wards are an important element in the mental healthcare of people at risk for acute harm to others or self-harm. Unfortunately, aggression, violence (conflict) and the use of coercion (containment) are still part of psychiatric care. The decisive factor for the correct handling of these situations is the quantity as well as the quality of the employees. Therefore, the present study dealt with the care situation on acute psychiatric wards. The hypothesis is that both the number of beds on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
4
0
8
Order By: Relevance
“…Die Antworten der Teilnehmenden decken sich damit mit den Befunden anderer Befragungen, dass Behandelnde in Krisensituationen vermehrt auf Medikamente [12,21,22] oder ZM zurückgreifen als auf andere potenziell hilfreiche MM [16,17]. Zudem stellen die Nennung von Verhaltensregeln, die Ankündigung einer drohenden ZM sowie der Überzeugungsversuch bereits informelle ZM dar [23] und sind damit nur eingeschränkt als MM zu zählen.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Die Antworten der Teilnehmenden decken sich damit mit den Befunden anderer Befragungen, dass Behandelnde in Krisensituationen vermehrt auf Medikamente [12,21,22] oder ZM zurückgreifen als auf andere potenziell hilfreiche MM [16,17]. Zudem stellen die Nennung von Verhaltensregeln, die Ankündigung einer drohenden ZM sowie der Überzeugungsversuch bereits informelle ZM dar [23] und sind damit nur eingeschränkt als MM zu zählen.…”
Section: Diskussionunclassified
“…Mittlerweile ist es unstrittig, dass das Risiko für eine ZM nicht ausschließlich von Merkmalen der betroffenen PatientInnen [8,11] abhängt, sondern von einer Vielzahl relevanter Einflussfaktoren wie der strukturellen Ausstattung und den Behandlungstraditionen der Kliniken selbst [12,13]. Ein ebenso relevanter Faktor ist ferner die Interaktion zwischen PatientInnen und pflegerisch-therapeutischen MitarbeiterInnen (= Behandelnde), welche die Eskalation im Vorfeld von ZM häufig maßgeblich beeinflusst [14].…”
Section: Introductionunclassified
“…Additionally, changes in the patient structure (e. g., more patients with needs for multimodal support by health care system and youth welfare system) and changes in society (e. g., more patients with divorced parents or patchwork families) were not recognized (APK, 2017;Beck, 2015;Koch-Stoecker & Kölch, 2020). Moreover, deescalative measures to avoid force and coercion toward patients became more important, including more talking-based interventions and 1:1 intensive care (Nienaber et al, 2018). Psych-PV was stopped by law on January 1, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of normative personnel requirements might lead to market-based decisions which counteract sensible, adequate, patient-and quality-oriented treatment (Godemann et al, 2015). Several studies showed that there is a connection between staffi ng levels and confl icts or other negative health outcomes (Blume et al, 2019;Nienaber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Importa ainda que todos os profissionais recebam formação, tanto na sua admissão como, no máximo, a cada 3 anos, sobre técnicas de prevenção da (Nienaber et al, 2018), 1 por publicação duplicada (Morrison, 1995) e dois por não analisarem influência do rácio (Allen, Fetzer & Cummings, 2020;Magnowski & Cleveland, 2019). Assim, incluíram-se 4 artigos na revisão qualitativa.…”
unclassified